Lived Experiences on Clinical Exposure among Nursing Students in Nepal - Basnet, Saraswati (Journal of Research and Development, 2025)
Clinical learning is a challenging aspect of nursing education which affords the nursing student an opportunity to practice the theory that is learned in classroom. The aim of this paper is to explore the lived experiences on clinical exposure of B.Sc. Nursing first year students. Qualitative phenomenological research design was used. The total sample size was 10 students based on the saturation of the information that was determined by the samples. Purposive sampling method was used for the selection of the samples. Face-face in-depth interview was taken with a help of semi-structured interview guide. Analysis of data was carried out by using the thematic analysis. The findings revel that the nursing students experience the inefficient communication, lack of team work, difficulty in socialization that increased their stress and anxiety in their workplace. In addition, language barrier, empty feeling towards patient care and discrimination in care. The study concluded with the nursing students experience insufficient knowledge, skill towards patient’s care which creates stress and anxiety among students. However, to provide support in the clinical learning may enhance knowledge and skill among students.